EVALUATION OF THE ENVIRONMENTAL RISK OF THE MIX OF ALPHA-CYPERMETHRIN AND IMIDACLOPRID ON THE EARTHWORM (EISENIA FETIDA) (SAVIGNY, 1826) - Arrázola-Vásquez, Elsa María (2021)
In the present study, the environmental risk (ERA) of alpha-cypermethrin and imidacloprid, individually and as a mixture, was evaluated on Eisenia fetida (Savigny, 1826). The mean lethal concentration (LC50) values for alpha-cypermethrin and imidacloprid individually were 341.1 mg·kg-1 and 2.34 mg·kg-1 at 14 d of exposure, respectively, being the most toxic imidacloprid. A reduction in dry and wet weight was observed in E. fetida, for both pesticides. The mixture did not show a significant dose-response relationship at LC50; However, the values of NOEC (concentration at which no effect is observed) and LOEC (lowest concentration at which effect is observed), corresponding to wet and dry weight, presented a significant relationship. The analysis of toxic units (TU) established an antagonistic behavior of both pesticides. The evasion test showed a relationship with the presence of the toxin in the mixture, however the same did not occur in the individual tests. In general, none of the chemical compounds is considered a highly toxic compound and they do not represent a significant risk at an acute level based on mortality for E. fetida, but sublethal effects could be presented in organisms due to growth impairment.